A comparative study between topical aluminium chloride hexahydrate 20% solution (Driclor) with potassium permanganate KMnO4 solution and topical zinc acetate with erythromycin (Zineryt solution) in treatment of axillary bromhidrosis - Hasan, Anwar Isaa; Latif, Tuqa Mohammed; Hasan, Ethar Falah (Journal of Pakistan Association of Dermatologists, 2023)
Objective ToÂ evaluateÂ andÂ compareÂ effectivenessÂ ofÂ topicalÂ combinedÂ driclorÂ solutionÂ with Potassium permanganate KMnO4 solution (1:10000) and topical zinc acetate with erythromycin (Zineryt solution) in treatment of axillary bromhidrosis. Â Methods Across-sectional comparative study was carried out from march 2021 to march 2022. Group A: 25 patients treated with Driclor single night application on dry clean axilla with KMnO4 solution (1:10000) single application at day time for 30 min then wash with tape water. Group B: 25 patients treated with topical zineryt solution twice daily applications for 12 weeks. Follow up of both groups for 12 weeks after stopping the treatment. Â Results Â There is no significant difference in mean of severity score for axillary bromhidrosis between group A and group B, before, after 6 weeks and after 12weeks.patients in group A show higher good satisfaction (72%) than group B(12%).during follow up period relapse rate was higher (72% (in group B in compare with relapse rate in group A (16%),percent reduction (response rate) for mean of severity score was 78.37Â±5.88% after 6 weeks and 91.89Â±35.29% after 12 weeks in group A and 61.76Â±4.08 % after 6 weeks and79.41Â±6.12% after 12 weeks in group B. Â Conclusion Both protocol was effective in treatment of axillary bromhidrosis, but topical driclor with Potassium permanganate KMnO4 solution (1:10000) show higher response rate and lower relapsing rate when compare with topical zineryt solution. Â